Analytic element modelling for strip aquifers - Batista, Jose Anderson N.; Wendland, Edson [UNESP]; Schulz, Harry E. [UNESP] (Wiley-Blackwell, 2012)
The Analytic Element Method (AEM) provides a convenient tool for groundwater flow analysis in unbounded continuous domains. The AEM is based on the superposition of analytic functions, known as elements, useful at both regional and local scales. In this study, analytic elements for strip aquifers are presented. Such aquifers occur in riverine or coastal deposits and in outcrop zones of confined aquifers. Local flow field is modelled indirectly, using a reference plane related to the aquifer domain through the Schwarz-Christoffel transform. The regional flow is obtained as a solution of the one-dimensional flow equation. The proposed methodology was tested by modelling two hypothetical situations, which were compared to exact solutions. It is shown that regional boundaries can be reproduced exactly while local fields are adequately reproduced with analytic elements. The developed elements are applied to simulate a real flow field in northeastern Brazil showing good agreement with measured water levels. Copyright (c) 2011 John Wiley & Sons, Ltd.
Keywords: strip aquifers; analytic element method; Schwarz-Christoffel transform